Hubungan antara Konformitas dengan Perilaku Konsumtif pada Mahasiswi di Jakarta - Rahmalika Putri Anjani; Marsofiyati Marsofiyati; Eka Dewi Utari (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Consumer behavior is a common phenomenon in urban communities, including among female students. This behavior is characterized by excessive purchases of goods without considering rational needs. One of the main factors influencing consumer behavior is social conformity, especially peer pressure. Female students often follow a consumer lifestyle to gain recognition from their social group. In addition, external factors such as culture, social class, family influence, and situations also play a role in shaping consumer behavior. This study aims to examine the relationship between conformity and consumer behavior in female students in Jakarta, by exploring the role of various social factors, including family influence. This study is expected to provide deeper insight into the social dynamics that influence consumer behavior and become the basis for more effective interventions in reducing consumer behavior in this age group.